Wujuudu Al-Lughah Al-'Arabiyyah Wa Masyaakiluhaa Al Ta'limiyyah Fi Al-'Ashriy Al-Tsauroti Al-Shinaa'iyyati 4.0 - Asfar Rinaldy (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
This study aims to find out how the problems and problems of learning Arabic in modern times are. This research uses a qualitative descriptive approach. And reports related to this issue. The data analysis technology used in this research is inductive data analysis. Building on the results of the research, the data found is the presence of Arabic in the era of the industrial revolution 4.0. This is because there are still many teachers and lecturers who use the old method in the Arabic learning process and maintain it, reducing the attention and motivation to learn Arabic among the general public and Arabic language specialist students in particular.